(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article covers the study of fixed phrases that name a person (woman or man) through the spectacle of vector modeling of gender marked names. The phrasicon image of a person is directed at reflecting the characteristics of the universal key concept of a person in the history of the culture of all common to humanity. In this context “a person in general” as a generic term is compared with other living beings; “a person – bearer of certain parameters and characteristics”, where there is a characteristic of personal qualities. Such statements are called universal because they are based on the verbal association of a person concept in the language conceptual framework. In phraseology the idioethnic signs are designated formally, forming a nationally idiosyncratic image. As conceptual entities, gender stereotypes reflected in the mental substratum of a linguistic sign, verbally objectified, preeminently in lexical nominations, since one of the key functions of the nomination process is to establish the relationship between the verbal shell and the mental processes reflected in consciousness. The conceptual picture of the world is not stable and is subject to continuous changes, which are associated with the influence of other cultures on the language, with technological progress and increased feminization. The new everyday items, the discovery of new living organisms and cosmic bodies, etc. open up new person names in phraseology. The fundamental of phraseological modeling is cognitive operations aimed at the interaction of the initial domain, which represents the sphere from which the cognitive attributes are borrowed, and the target domain is an abstraction, which is identified using phraseological locutions.